FUNCTIONAL AND PSYCHO-SOCIAL ISSUES IN ACUTE CARE: DATA FROM THE “NEW” INTERRAI ACUTE CARE - Gray, L.C. (Innov Aging, 2017)
The interRAI Acute Care is a new assessment system designed to identify functional and psychosocial problems among adult patients admitted to acute care. It comprises 52 clinical observations and a series of algorithms that perform diagnostic and risk screening, measure problem severity (scales) and assess quality of care. We undertook a study to determine the frequency distributions of the clinical observation among adult patients across 4 hospitals in Australia: A large tertiary hospital, a medium size community hospital, and 2 small rural hospitals. Assessments were performed by trained nurses with 12 hours of admission to an inpatient unit. The sample comprised 837 subjects, of whom 359 (43%) were aged > 70 years. While the prevalence of these problems was high, as expected, among older patients, there were some problems that were unexpectedly prevalent among younger patients. For example, short term memory problems were present in 6% of patients aged 18–29 and 22% among those aged 40–49, compared to 37% among older patients. Similar patterns of high prevalence was present for mood disturbances, balance problems, falls, pain, sleep disorders and basic activities of daily living. We concluded that functional and psychosocial problems are sufficiently prevalent among younger hospitalised patients that universal screening is warranted for all adult patients.